(untitled) (Global Journal of Management and Business Research, 2020)
Payment of Tax is a compulsory levy by the Government of a country on its citizens to raise money for the public good. This study examined the mode of Assessment, Collection, and Accountability of Personal Income Tax in Akwa Ibom State using Uyo Local Government Area as a case study. The study aimed to ascertain the problems deterring effective tax administration culminating in the un-realization of budgeted tax revenues in Akwa Ibom State. To achieve research objectives, primary and secondary data were swotted and research hypotheses formulated and questionnaires administered accordingly. The research hypotheses were tested using the Chi-square (χ2) Statistics. The results revealed that the methods and procedures adopted by the Tax Officers for assessing, collecting and accounting for Personal Income Tax were not appropriate enough to enhance effective tax administration to bring adequate tax returns.